From "state control" to "business lobbying": The institutional origin of private entrepreneurs' policy influence in China - Dongya Huang; Minglu Chen; Thomas Heberer (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2017)
Existing scholarship regards the collusion between the Chinese government and the private sector as 'informal' and a series of 'economic alliances', without considering the private sector's institutionalized participation in the process of government policy formulation. This article takes an alternative perspective and examines such institutionalized efforts in interest expression and policy promotion. In the authoritarian regime, state institutions that previously functioned to co-opt and corporatize the private sector have also become forums in which private entrepreneurs can have an impact on policy-making. This change results from the state's initiative in developing formal channels of participation based on the united front work remnant and interaction between 'state control' and the 'business lobby'. The shift from 'state control' to the 'business lobby' reveals a unique pathway for private interest to have an impact on public policy formulation.
Keywords: 330; business lobbying; All-China Federation of Industry and Commerce; business associations; Chinese Political Consultative Conference